Determinants, reproducibility, and seasonal variation of ergosterol levels in house dust. (21st December 2013) - Leppänen, H. K.; Nevalainen, A.; Vepsäläinen, A.; Roponen, M.; Täubel, M.; Laine, O.; Rantakokko, P.; von, E.; Pekkanen, J.; Hyvärinen, A.
Abstract This study aimed to clarify the determinants that affect the concentrations of ergosterol and viable fungi in house dust and to examine the seasonal variation and reproducibility of ergosterol concentrations indoors. In studying the determinants, dust samples from living room floors and vacuum cleaner dust bags were collected from 107 farming and 105 non‐farming homes. Ergosterol levels were determined with gas chromatography‐mass spectrometry, and the dust bag dust was cultivated for enumeration of fungal genera. Lifestyle and environmental factors, for example using of the fireplace, and visible mold observations in homes, explained 20–26% of the variation of fungal concentrations. For the reproducibility study, samples were collected from five urban homes in four different seasons. The reproducibility of ergosterol determinations within a sample was excellent (ICC = 89.8) for floor dust and moderate (ICC = 63.8) for dust bag dust, but poor when sampling the same home throughout a year (ICC = 31.3 and 12.6, respectively) due to large temporal variation in ergosterol concentrations. In conclusion, environmental characteristics only partially predicted the variation of fungal concentrations. Based on these studies, we recommend repeated sampling of dust over time if one seeks to adequately describe overall fungal levels and exposure in a home.